Quantifying the global binding and target-search dynamics of epigenetic regulatory factors using live-cell single-molecule tracking - Kyle Brown (Elsevier, 2021)
Summary: This protocol provides instructions to track the global dynamics of single epigenetic regulatory factors in live cells. We describe an approach to generate cell lines that stably express HaloTag-fused proteins. We then use live-cell single-molecule tracking to obtain kinetic populations and residence times. The kinetic parameters obtained can be used to determine important aspects of transcriptional regulation such as target-search time, 3D free diffusion time, and number of non-specific sites sampled before reaching a specific site and compare behaviors across different nuclear environments.For complete details on the use and execution of this protocol, please refer to Kent et al. (2020).